Neurocardiac Transfer: Effects of Aerobic Exercise Training on the Neurocardiac Responses to Exercise and Exercise Recovery with the Untrained Limbs - Huggins, James (My University, 2000)
There have been many attempts at answering the question of whether the cardiovascular adaptations resulting from aerobic exercise training of a particular muscle group are transferable when exercise is performed with the untrained muscles? Through the use of power spectral analysis (PSA) of heart rate variability (HRV) and blood pressure variability (BPV) the present study investigated this question in terms of a training induced modification of neurocardiac control. Fifteen healthy subjects (7 arm trainers & 8 leg trainers) aerobically exercise trained for 9 weeks, 3 sessions/week for 45 minutes/session. Training workload intensities were selected individually to obtain a target training heart rate (HR) between 75-80% HR maximum as determined from the initial pre-training V0₂ₘₐₓ. of the respective limbs. The exercise training program had no effect on supine rest HR, HR V or BPV, or standing HR and HRV. Following training, the arm group demonstrated a significant increase in V0₂ₚₑₐₖ (30.0 ± 1.4 to 34.2 ± 1.8 ml/kg/min.; p<0.05) during arm exercise and a significant reduction in leg exercise V0₂ₚₑₐₖ ( 44.8 ± 2.1 to 41.2 ± 1.6 ml/kg/min.; p<0.05). The leg training group demonstrated a slight post-training increase in leg exercise V0₂ₚₑₐₖ (43.5 ± 1.7 to 44.2 ± 2.4 ml/kg/min.; N.S.) and no change in arm exercise V0₂ₚₑₐₖ. Post-training changes in the maximum power produced during the respective limb group exercise tests corresponded to those of V0₂ₚₑₐₖ results. Mean HR values obtained from the arm trained group during the progressive maximal arm exercise test demonstrated significant post-training reductions at 50 percent (Δ-13 ±3.0 b.p.m.;p<0.05) and 75 percent (Δ-16 ± 5.8 b.p.m.;p<0.05) of the pre-training maximum workload. No change in mean HR was observed during progressive leg exercise in the arm trained group. The leg training group demonstrated non-significant HR reductions in both arm (Δ-3 ± 3.1 b.p.m. at 50% & Δ-6 ± 2.8 b.p.m. at 75%; N.S.) and leg (Δ -6 ± 4.5 b.p.m. at 50% & Δ -9 ± 3.5 b.p.m. at 75%; N.S.) progressive exercise tests. Mean HR and indices of HRV and BPV measured over 15 minutes of recovery following maximal exercise of both limb groups, were unaffected as a result of either training modality. The leg trained group demonstrated non-significant reductions in mean HR during both arm and leg steady-state submaximal exercise tests following training. No significant changes in any HRV components were observed in concordance with these non-significant mean HR reductions. Similarly, the arm trained group failed to demonstrate any significant changes in mean HR or HRV indices during either arm or leg submaximal exercise. Results from the present investigation indicated that a positive exercise training effect had occurred in the arm trained group, while the leg training group demonstrated smaller improvements in exercise performance compared to the arm trainers. Findings from the incremental exercise test further demonstrated the post-training improvements in the arm training group, and negligible improvements within the leg trained group. These improvements, or lack of, were all demonstrated in the mean HR measure with no significant changes in HRV patterns. This would suggest that non-neural factors contributed to most of the post-training adaptations. The discrepancies in results between the two training groups may be attributed firstly to the arm muscles greater potential for peripheral adaptations. Secondly, an inadequate training stimulus for the leg training group probably resulted in their poor post-training improvements. Lastly, the low submaximal exercise test intensities may have limited a clear observation in training improvements of either limb training group. The examination of post-maximal arm and leg exercise recovery failed to disclose any new information on the neurocardiac influences during exercise recovery subsequent to upper or lower limb training. The question of whether training induced neurocardiac control modifications may be transferable between the trained and untrained limbs may still be relevant, but requires more vigorous training of either muscle group.
Keywords: aerobic training; neurocardiac transfer; exercise